Bali’s Customary Criminal Justice System and the Draft Criminal Procedure Code in the Context of National Legal Harmonization in Indonesia - Candra, Septa; Prakarsa, Aliyth; Nur, Rafi Dwi Fathurahman (Universitas Muhammadiyah Purwokerto, 2026)
Customary criminal justice in Bali is a form of dispute resolution based on local values that has long existed in society, but its existence faces serious challenges in the process of harmonization with the national legal system, particularly in the context of the Draft Criminal Procedure Code (RKUHAP). This study aims to examine the position and role of Balinese customary justice within the framework of the RKUHAP and to assess the extent to which customary justice can be integrated without eliminating local legal identity. The method used is a juridical-normative with a conceptual and legislative approach, and is complemented by a juridical-comparative analysis of the provisions in the Balinese Customary Court, the National Criminal Code and the RKUHAP. The results of the study indicate that although there is recognition of customary law in legislation, the position of customary justice is still subordinate and has not received strong institutional guarantees in the RKUHAP. Legal harmonization requires more affirmative regulations for customary justice so that its existence is not merely symbolic. Therefore, a legal formulation is needed that can accommodate customary justice as an integral part of the national criminal justice system, based on the principles of restorative justice and legal diversity. This study recommends that the Criminal Procedure Code (RKUHAP) explicitly regulate the mechanisms and limits of customary justice authority, as well as provide equal formal recognition for its role in resolving community-based criminal cases.